"The Dawn of Wonder? An Italian Experience of Teaching Philosophy to Children. - Zippel, N.
The Dawn of Wonder? is a philosophical laboratory that the author, a high school philosophy teacher, has for many years led in several elementary schools in Rome. The paper aims at presenting the main characteristics of such experience of teaching philosophy to children, which doesn?t adopt the methodology of Philosophy for Children, but develops an original approach based on a historical narration of ideas and thinkers coming from both Western and Eastern traditions. According to this perspective, teaching philosophy to children means dealing with theoretical issues by keeping them in their historical and geographical context. In this way, a child who meets philosophy can reason on the basic problems of human understanding without losing sight of their geo-historical origins.
Keywords: Philosophy -- Periodicals